2017
DOI: 10.1002/hbm.23736
|View full text |Cite
|
Sign up to set email alerts
|

Cortical connectivity modulation during sleep onset: A study via graph theory on EEG data

Abstract: Sleep onset is characterized by a specific and orchestrated pattern of frequency and topographical EEG changes. Conventional power analyses of electroencephalographic (EEG) and computational assessments of network dynamics have described an earlier synchronization of the centrofrontal areas rhythms and a spread of synchronizing signals from associative prefrontal to posterior areas. Here, we assess how "small world" characteristics of the brain networks, as reflected in the EEG rhythms, are modified in the wak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 41 publications
2
40
2
Order By: Relevance
“…Indeed, during this particular period of wakefulness, there is a gradual decrease in the high-frequency EEG bands (β and α) and a gradual increase in the low-frequency EEG bands (δ) in order to prepare the sleep-wake transition [73]. However, the presence of these modifications in the frequency bands during this period preceding sleep onset seems to be associated with a more efficient antero-posterior cerebral communication favouring a more marked SWN organization in both men and women [74]. Furthermore, we demonstrated that compared to men, women had a greater sleep latency and a shorter sleep period time which seems to indicate the presence of reduced sleep duration in women.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, during this particular period of wakefulness, there is a gradual decrease in the high-frequency EEG bands (β and α) and a gradual increase in the low-frequency EEG bands (δ) in order to prepare the sleep-wake transition [73]. However, the presence of these modifications in the frequency bands during this period preceding sleep onset seems to be associated with a more efficient antero-posterior cerebral communication favouring a more marked SWN organization in both men and women [74]. Furthermore, we demonstrated that compared to men, women had a greater sleep latency and a shorter sleep period time which seems to indicate the presence of reduced sleep duration in women.…”
Section: Discussionmentioning
confidence: 99%
“…One strength is the use of PLI to measure FC, since it reduces the bias due to volume conduction and activity from common sources (Stam et al, ). Another strong point is that when we compared the differences of global PLI and MST measures between groups, age, sex and the power of each frequency band were taken into consideration as covariates (Vecchio et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Functional connectivity was computed by eLORETA software (available at http://www.uzh.ch/keyinst/loreta) on 84 regions of interest (ROIs) de ned according to the 42 Brodmann areas (BAs) in the left and right hemispheres. The signal at each ROI was the average electrical neuron activity of all voxels in the ROI [32]. Among the eLORETA current density time series of the 84 ROIs, lagged linear connectivity [33] was computed between all possible pairs of the 84 ROIs for the alpha band for each subject.…”
Section: Functional Connectivity Analysismentioning
confidence: 99%